Food Joints Along Selected National Highways in Haryana: A Spatio-Temporal Analysis - Singh, Karam; Kaushik, S. P. (National Geographical Journal of India, 2022)
The present study shows the growth process and spatial pattern of food-joints along nationai highway-1, 2, 8 and10 falling in Haryana. The objective of the study is to analyze the spatial pattern and temporal growth of food-joints i.e. hotels, restaurants, dhabas, wine-shops and other facilities. The present study is based on both qualitative and quantitative data. The data have been analyzed with the help of simple statistical techniques. The study reveals tremendous growth of food-joints after 1991.The study points out that NH-1 and NH-10 have more concentration of highway food-joints facilities; however, the later has maximum number of facilities largely in big cities. Before, 1991 these facilities were available mainly in towns and cities, but after, 1991 there was a wide distribution of these facilities all along the highways. It is found that hotel and restaurant facilities are mainly concentrated in cities and towns. It seems that the volume of traffic directly affected the concentration of these services.